War crimes in the International Criminal and Humanitarian Law and in the Criminal Law of Ukraine: theoretical and practical aspects - S. V. Shcherbak (Bulletin of Kharkiv National University of Internal Affairs)
The article reveals the criminal law characteristics of war crimes in the International Criminal Law, International Humanitarian Law and under the National Criminal Law. The category of “war crimes” is analysed and its Criminal Law description is made in terms of substantive, international and national components in the context of combining theoretical and applied aspects of war crimes research. A comparative analysis of war crimes in both International Criminal Law and National Criminal Law has been made, with the examples of application of Article 438 of the CC of Ukraine from judicial practice provided, and the legislative regulation of the term “war crimes” in the CC of Ukraine has been proposed, given the trend of clear separation of the category of war crimes which has been observed since the beginning of the armed conflict in Ukraine in the National Criminal Law science and in law application which remains doctrinal.